The effects of laboratory ageing on rheological and fracture characteristics of different rubberised bitumens - Subhy, Ayad; Pires, Gustavo Menegusso; Lo Presti, Davide; Airey, Gordon (Elsevier, 2018)
Ageing of bituminous materials can result in loss of the durability of a flexible pavement. Using rubberised bitumens can enhance pavement performance while at the same time it solves a serious waste disposal problem. Combining Warm Mix Asphalt (WMA) additives with rubberised bitumens reduces the difficulties associated with the production of asphalt mixtures using this modified binder. This work was conducted to study the effect of ageing using fundamental parameters based on performance, i.e., CTOD and Glover-Rowe parameters have been related to pavement cracking. Different unmodified bitumens and rubberised bitumens were short-term aged using the Thin Film Oven Test (TFOT) and long-term aged using the Pressure Ageing Vessel (PAV). The rheological and fracture properties of the binders were studied before and after laboratory ageing. The results indicated that rubberized bitumens are more resistant to laboratory ageing. However, the pre-treatment with Sasobit® seemed to be detrimental when the materials were evaluated based on their fracture properties. The results also showed that base bitumen properties can affect the ageing mechanism of rubberised bitumens. Using softer bitumen could produce rubberised bitumens with superior anti-ageing properties when the analysis is based on linear viscoelastic properties using the Glover-Rowe parameter. However, these improvements were significantly reduced after ageing when the analysis is based on fracture properties.